Development of Nanocomposites based on Layered Double Hydroxides and graphene-like materials - Magri, Vagner Roberto (2023)
Nanocomposites based on layered double hydroxides (LDH) and graphene-like materials (C), e.g., graphitic carbon and carbon quantum dots (C-dots), have been applied in sensing, catalysis, environmental protection, electronic devices, and as bioimaging and theragnostic agents, for instance. In this work, hybrid materials constituted of M2Al-LDH (M = Mg2+ or Zn2+) intercalated with carboxymethylcellulose polymer (CMC) or folate anions from Folic Acid (FA) were synthesized and investigated as precursors of carbon-based materials. Their thermal behavior was evaluated by simultaneous thermogravimetric analysis (TGA) and differential scanning calorimetry (DSC), as well as evolved gas analysis (EGA) through TGA coupling to mass spectroscopy (MS) and/or infrared spectroscopy (IR). Based on the TGA/DSC results, the materials were pyrolyzed in a furnace, and resulting nanocomposites were structurally and spectroscopically characterized. The main founds of the work were: (i) M2AlFA and M2Al-CMC were suitable sources of carbon-based nanocomposites composed of layered double oxides (LDO-C); (ii) from pyrolysis of FA itself, N-doped C-dots could be synthesized at 350 °C, whereas graphitic carbon was optimally obtained above 800 °C; (iii) the carbonization of folate anions was delayed after intercalation; (iv) vibrational spectroscopy characterization of FA and sodium folate salts (Na2HFol and Na3Fol), supported by density functional theory (DFT) calculations, were helpful in characterize related graphite-like materials and carbon-based nanocomposites; (v) the crystallization of metal oxides (i.e.; MgO and ZnO) and/or spinel-like structures (i.e., MgAl2O e ZnAl2O) were hindered for M2Al-LDH hybrid materials when compared with their counterparts intercalated with simple anions, for instance, carbonate (CO3-) and chloride (Cl-). Such hindrance was attributed to the carbonized matter formed during pyrolysis; (vi) for Zn2Al-LDH hybrids material, it was noticed a carbothermic reaction involving ZnO occurring above 800 °C, which led to the loss of zinc vapor; (vii) LDO-C obtained from M2Al-FA pyrolysis could be successfully restored into the LDH-C structure through reaction in water (\"memory effect\"). Nanocomposites presenting intimately mixed components were obtained up to 600 and 800 °C from Zn2Al-FA and Mg2AlFA precursors, respectively; (viii) LDH-FA were also potential precursors of nanocomposites based on LDH/C-dots and the proper temperature limit was determined to be around 400 °C. The exploration of nanocomposite precursors with different physicochemical properties allowed us to provide a wide-ranging knowledge of important features regarding the synthesis of nanocomposites based on LDH and graphene-like materials. Hence, this research can drive new strategies to synthesize LDH-C and LDO-C with assorted potential applications.